Scientific production on para athletics: a bibliometric review - Garcia-Carrillo, E.; Ramirez-Campillo, R.; Winckler, C. (International Journal of Disabilities Sports and Health Sciences, 2024)
Background: A comprehensive evaluation of the scientific production in the sport of Para Athletics, encompassing both quantity and quality, is lacking. Aim: To perform a quantitative and qualitative bibliometric analysis using science mapping techniques, to investigate publication trends, author network clusters, and keyword occurrence linked to the scientific production in the PA sport. Methods: Studies related to PA were identified throughout a search across the databases PubMed, Scopus, and Web of Science (Core Collection). Results: From an initial pool of 2,350 documents, 149 were deemed eligible and incorporated into the study. Most studies were published in the last 10 years, mainly in journals related to the fields of Sport Sciences and Rehabilitation. The keyword analysis revealed 364 unique keywords, 8 distinct clusters, 287 connections. Bibliometric examination unveiled 21 authorship network clusters, comprising 260 links. Countries that contributed with most research (75.7% of all published articles) includes United States, Canada, Brazil, United Kingdom, Germany, Netherlands, Spain, South Africa, Japan, and Australia. Conclusion: Research related to PA has increased exponentially in recent years, particularly in the fields of Sport Sciences and Rehabilitation. Collaborative research (authorship network clusters) seems prevalent, and all continents demonstrated participation in published studies, albeit with different relative contributions.